1997
DOI: 10.1002/(sici)1099-0844(199709)15:3<203::aid-cbf742>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of citrinin-induced dysfunction of mitochondria. V. Effect on the homeostasis of the reactive oxygen species

Abstract: The effects of citrinin in the maintenance of the homeostasis of the reactive oxygen species in rat liver cells were evaluated. Citrinin (CTN) modifies the antioxidant enzymatic defences of cells through the inhibition of GSSG-reductase and transhydrogenase. No effect was observed on GSH-peroxidase, catalase, glucose 6-phosphate and 6 phosphogluconate dehydrogenases, and superoxide dismutase. The mycotoxin increased the generation of reactive oxygen species, stimulating the production of the superoxide anion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 36 publications
3
29
0
1
Order By: Relevance
“…Martin et al (1986) reported that oxidative stress played a great role in causing CIT toxicity as CIT induced single-and double-strand breaks in the DNA of intact Escherichia coli and this activity was prevented by catalase and SOD, suggesting the involvement of free radicals in the mechanism of CITinduced damage. Ribeiro et al (1997), however, did not observe any significant role of oxidative stress in CIT toxicity on rat liver cells. In another study in rabbits, it was observed that CIT alone did not cause any significant change in antioxidant enzymes (SOD and catalase), but in combination with OTA, the effect was more severe (additive) (Kumar, 2005) than that observed when OTA alone was used.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al (1986) reported that oxidative stress played a great role in causing CIT toxicity as CIT induced single-and double-strand breaks in the DNA of intact Escherichia coli and this activity was prevented by catalase and SOD, suggesting the involvement of free radicals in the mechanism of CITinduced damage. Ribeiro et al (1997), however, did not observe any significant role of oxidative stress in CIT toxicity on rat liver cells. In another study in rabbits, it was observed that CIT alone did not cause any significant change in antioxidant enzymes (SOD and catalase), but in combination with OTA, the effect was more severe (additive) (Kumar, 2005) than that observed when OTA alone was used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that citrinin, an antibacterial substance produced by Monascus species has a strong inhibitory effect against gram-positive bacteria (Su et al, 2003;Vendruscolo et al, 2014). Our investigation is also in agreement with the results of the M. purpureus NTU 601 strain proven to produce citrinin (Ribeiro et al, 1997) which postulated that the antibacterial effect of citrinin on B. subtilis was related to the size of the inhibition zone. So, it was observed that Monascus pigment besides colour provides preservation value.…”
Section: Antimicrobial Activity Of the Pigmentmentioning
confidence: 99%
“…Industrially, Monascus species is an important source of bioactive compounds like monacolin K, which is a very effective hypocholesterolemic agent. However, a toxic drug interaction has been reported between cyclosporine and monacolin K of the red yeast rice (Monascus purpureus) that led to rhabdomyolysis in a renal transplant recipient [6][7][8][9][10]. Some Monascus compounds such as citrinin have been reported to be nephron-hepatotoxic [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is known to cause gastric infection that is associated with the consumption of contaminated dried and salted fish as M. ruber is sodium chloride tolerant [6,7]. It has also been reported to cause allergy and anaphylaxis in response to red yeast rice which is due to an immediate sensitivity to Monascus purpureus [9]. Another study described a direct renal infection due to M. ruber after surgery in a 70-year-old patient with multiple kidney stones [4].…”
Section: Discussionmentioning
confidence: 99%